2018
DOI: 10.3390/cells7110217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of TQ-6, a Novel Ruthenium-Derivative Compound, against Lipopolysaccharide-Induced In Vitro Macrophage Activation and Liver Injury in Experimental Mice: The Crucial Role of p38 MAPK and NF-κB Signaling

Abstract: Several studies have reported that metal complexes exhibit anti-inflammatory activities; however, the molecular mechanism is not well understood. In this study, we used a potent ruthenium (II)-derived compound, [Ru(η6-cymene)2-(1H-benzoimidazol-2-yl)-quinoline Cl]BF4 (TQ-6), to investigate the molecular mechanisms underlying the anti-inflammatory effects against lipopolysaccharide (LPS)-induced macrophage activation and liver injury in mice. Treating LPS-stimulated RAW 264.7 cells with TQ-6 suppressed nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Given the reduced pro-inflammatory cytokine secretion mediated by rGDF3, we next tested whether GDF3 influenced macrophage phenotype. RT-PCR analysis of macrophage polarization markers (i.e., iNOS for M1 and Arg1 for M2) showed that LPS stimulation remarkably activated iNOS expression, whereas greatly inhibited Arg1 expression in BMDMs ( Figure 4A,B), which are consistent with previous reports [19]. However, treatment of LPS-macrophages with rGDF3 resulted in a significantly reduction of iNOS expression ( Figure 4A) and elevation of Arg-1 mRNA levels ( Figure 4B), compared to control cells.…”
Section: Gdf3 Inhibits Lps-mediated Macrophage Pro-inflammatory Polarsupporting
confidence: 92%
“…Given the reduced pro-inflammatory cytokine secretion mediated by rGDF3, we next tested whether GDF3 influenced macrophage phenotype. RT-PCR analysis of macrophage polarization markers (i.e., iNOS for M1 and Arg1 for M2) showed that LPS stimulation remarkably activated iNOS expression, whereas greatly inhibited Arg1 expression in BMDMs ( Figure 4A,B), which are consistent with previous reports [19]. However, treatment of LPS-macrophages with rGDF3 resulted in a significantly reduction of iNOS expression ( Figure 4A) and elevation of Arg-1 mRNA levels ( Figure 4B), compared to control cells.…”
Section: Gdf3 Inhibits Lps-mediated Macrophage Pro-inflammatory Polarsupporting
confidence: 92%
“…Further study supported TQ inhibiting NF-kappaB and NO activation [44]. Consistent with this finding, [53] reported that TQ inhibited NO production by reducing the expression of iNOS to reveal its anti-inflammatory response. It has been suggested that by inhibiting COX, NO, and NF-kappaB, TQ has strong anti-inflammatory potential.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, treatment with the metal compound with dietary intervention displayed more effective results in terms of lowering ALT levels in prediabetic rats. A recent study by Hsia et al 22 demonstrated the anti-inflammatory properties of a novel ruthenium compound, via inhibiting inflammatory mediators (nitric oxide and nitric oxide synthase) and proinflammatory cytokines (tumor necrosis factor-α and interleukin-1β)in RAW 264.7 cells. Additionally, the metal compound also displayed protective effect against lipopolysaccharide-induced liver injury in mice, thus protecting progressive liver damage 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hsia et al 22 demonstrated the anti-inflammatory properties of a novel ruthenium compound, via inhibiting inflammatory mediators (nitric oxide and nitric oxide synthase) and proinflammatory cytokines (tumor necrosis factor-α and interleukin-1β)in RAW 264.7 cells. Additionally, the metal compound also displayed protective effect against lipopolysaccharide-induced liver injury in mice, thus protecting progressive liver damage 22 . Moreover, the findings of the study could suggest that the integration of the Schiff base ligand within the coordination sphere of this ruthenium(II) complex could possibly protect the liver from toxic and proinflammatory effects because metal compounds complexed with organic ligands have been found to be less toxic 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation